Rockets and feathers: Asymmetric pricing and consumer search - Evidence from electricity retailing - Sven Heim (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
Recent theories suggest that consumers' search efforts are a function of prices and prices changes, respectively. This may help to explain the 'rockets and feathers' phenomenon often assigned to collusion - prices rise like rockets when costs increase and fall like feathers when costs decrease. This paper empirically investigates the relation between cost pass-through and consumer search intensity for the German electricity retail market utilizing a unique panel dataset on retail electricity prices and consumer search intensity at online comparison sites for retail electricity, both at the zip code level. The main findings are 1) consumers search non-linear with regard to prices and price changes. They search more when prices are high and they decrease search efforts substantially when prices fall but only increase search efforts slightly when prices rise, 2) costs are passed-through asymmetrically with positive cost shocks causing higher pass-through rates than cost decreases and 3) search intensity significantly impacts price adjustments and controlling for search intensity eliminates large parts of the asymmetry. I compare this finding with a counterfactual - the entrants - where all consumers are fully informed. In this case consumer search does not affect cost pass-through.
urn:nbn:de:bsz:180-madoc-415566; Is replaced by the following version: http://hdl.handle.net/10419/193704
Keywords: D83; L11; 330; Information; Cost Pass-through; Consumer Search; Rockets and Feathers